Psychometric properties of the Collective Efficacy Scale Short-Form in Chilean teachers - Herrera, Camilo; Torres-Vallejos, Javier; Martínez-Libano, Jonathan (Frontiers in Psychology, 2022)
Background The Collective Efficacy Scale Short-Form (CES-SF) is a short and reliable instrument that assesses collective efficacy in schools at a group level. Previous research has shown a two-factor structure considering the perception of the group competence about their teaching capabilities and task analysis that refers to the opportunities inherent to a specific task. However, there is no conclusive evidence that collective efficacy corresponds to a two-factor model or single-factor structure. Methods A cross-sectional research was conducted on a 693 sample of teachers (Mage = 39.4; SD = 11.8) from schools in the 16 regions of Chile. They were assessed using the CES-SF, Personal Well-being Index, Social Well-Being Scale, and satisfaction with the school. Exploratory and confirmatory factor analyses were used to assess the construct validity of the CES-SF. Results The CES-SF showed mixed results about its construct validity. Best fit has been found to retain two new factors (opportunities and challenges for collective efficacy) with eight items each, yielding a McDonald’s ω of 0.803. Convergent validity was also established. Conclusion The psychometric results suggest that a two-factor structure for the CES-SF is a valid and reliable measure for this construct for Chilean teachers. However, collective efficacy might not strongly relate to subjective wellbeing but to school-context variables.